2010
DOI: 10.2147/opth.s15952
|View full text |Cite
|
Sign up to set email alerts
|

Long-term safety and efficacy of selective laser trabeculoplasty as primary therapy for the treatment of pseudoexfoliation glaucoma compared with primary open-angle glaucoma

Abstract: PurposeTo investigate the safety and efficacy of selective laser trabeculoplasty (SLT) to reduce intraocular pressure (IOP) in patients with pseudoexfoliation glaucoma (PXFG) compared with primary open-angle glaucoma (POAG).DesignNon-randomized, prospective, clinical trial.MethodsNineteen eyes of 13 patients with POAG and 18 eyes of 13 patients with PXFG were treated with SLT. Patients were followed without antiglaucoma medications until additional medical, laser, or surgical intervention was initiated, at whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
55
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(62 citation statements)
references
References 5 publications
5
55
1
1
Order By: Relevance
“…2 SLT has been established to be a safe procedure with few known side effects including post-procedure intraocular pressure (IOP) elevation, blurred vision, ocular irritation and iritis, all of which are generally transient, lasting no more than a few days. [3][4][5][6][7][8] Permanent corneal changes after SLT are extremely rare with only two reported cases 9 in the literature of corneal edema, haze, and thinning occurring within 24-48 h post laser. These cases resulted in irreversible corneal scarring, thinning, and a myopic shift in refractive error.…”
Section: Introductionmentioning
confidence: 99%
“…2 SLT has been established to be a safe procedure with few known side effects including post-procedure intraocular pressure (IOP) elevation, blurred vision, ocular irritation and iritis, all of which are generally transient, lasting no more than a few days. [3][4][5][6][7][8] Permanent corneal changes after SLT are extremely rare with only two reported cases 9 in the literature of corneal edema, haze, and thinning occurring within 24-48 h post laser. These cases resulted in irreversible corneal scarring, thinning, and a myopic shift in refractive error.…”
Section: Introductionmentioning
confidence: 99%
“…When evaluating patients with OAG or ocular hypertension (OHT) treated with SLT, Melamed et al (33) observed a ≥19.6% IOP reduction in 89% of the patients, while Mahdy (29) found an IOP-reduction ≥25% in 77.1% of the cases. Overall, in an attempt to summarize IOP data from the available studies, we found that average absolute IOP-reduction following SLT as first treatment ranges from 3 to 8 mmHg (percentage IOP reduction: 20% to 38%) (17,18,29,31,33,34) . Other studies compared SLT versus PGA as a primary therapy, with similar efficacy between the two treatment modalities (16)(17)(18) .…”
Section: Efficacy (Iop Reduction)mentioning
confidence: 98%
“…As PGAs are the first line clinical treatment to OAG, most studies compared SLT with PGA results in terms of IOP reduction. Looking carefully at safety and efficacy outcomes of these studies, we believe there is growing evidence that SLT can be used as a primary treatment for IOP-control in OAG cases (17,(28)(29)(30)(31)(32)(33) . Table 2 provides a summary of the main results of these studies.…”
Section: Efficacy (Iop Reduction)mentioning
confidence: 99%
See 2 more Smart Citations